Glycogen synthase kinase-3 regulates inflammatory tolerance in astrocytes - Beurel, Eléonore (2010)
Inflammatory tolerance is the down-regulation of inflammation upon repeated stimuli, which is well-established to occur in peripheral immune cells. However, less is known about inflammatory tolerance in the brain although it may provide an important protective mechanism from detrimental consequences of prolonged inflammation, which appears to occur in many psychiatric and neurodegenerative conditions. Array analysis of 308 inflammatory molecules produced by mouse primary astrocytes after two sequential stimulations with lipopolysaccharide (LPS) distinguished three classes, tolerant, sensitized and unaltered groups. For many of these inflammatory molecules, inhibition of glycogen synthase kinase-3 (GSK3) increased tolerance and reduced sensitization. Focusing on LPS-tolerance in interleukin-6 (IL-6) production, we found that microglia exhibited a strong tolerance response that matched that of macrophages, whereas astrocytes exhibited only partial tolerance. The astrocyte semi-tolerance was found to be regulated by GSK3. GSK3 inhibitors or knocking down GSK3 levels promoted LPS-tolerance and astrocytes expressing constitutively active GSK3 did not develop LPS-tolerance. These findings identify the critical role of GSK3 in counteracting IL-6 inflammatory tolerance in cells of the CNS, supporting the therapeutic potential of GSK3 inhibitors to reduce neuroinflammation by promoting tolerance.